Symposium 5: Stories About Innovative Processes In Higher Education: Some Success Factors - Charlier, Bernadette; Platteaux, Hervé; Bouvy, Thérése; Esnault, Liliane; Lebrun, Marcel; Moura, Ana; Pirotte, Sébastien; Denis, Brigitte; Verday, Nathalie (Proceedings of the International Conference on Networked Learning, 2004)
Previous studies have explored e-learning innovation in higher education from a number of different perspectives: virtual campus implementation, ICT in higher education, web-based learning and teaching, and teacher training. Our research aims to study the processes of pedagogical and technological innovation (for example e-learning, blended learning, collaborative learning, constructivist scenarios) and thereby to identify some key factors in these processes, with particular emphasis on the factors for success at the institutional level.